Agrobacterium-mediated transformation and in vitro evaluation of dehydration tolerance in transgenic tobacco harboring Ca-AFP gene - Ngoc Ha, Tran Thi; Van Duong, Hoang; Cam Tu, Nguyen Huynh; Tuong Loc, Phan (Vietnam Journal of Biotechnology, 2022)
We have known that plant defensins have the main roles in biotic stress, especially antifungal activities. In addition, their functions on abiotic stress tolerance have been demonstrated on previous studies, but that information was still limited. Ca-AFP, a plant defensin gene derived from chickpea, was transformed into tobacco leaf disks by Agrobacterium method. After 16 weeks on selection media containing 15 mg/L hygromycin, some regeneration shoot lines were obtained. Four of them showed the positive bands on hpt gene and Ca-AFP gene by PCR screening. These lines were applied on in vitro evaluation of dehydration tolerance using rotary liquid culture, and the water-deficit stress was caused by 2% (w/v) PEG 6000. These four transgenic lines had better growth of adventitious roots (number of adventitious roots, total adventitious root length, and average of root length) and higher rate of biomass increase than the non-transgenic line. The result illustrated that the expression of Ca-AFP gene could mitigate the negative effect of water-deficit stress on transgenic tobacco lines under the in vitro stress condition. These transgenic tobacco lines are potential for water-deficit stress trials on greenhouse in the future.